(untitled) (The Review of Diabetic Studies, 2015)
Diabetes mellitus results from a deficiency or failure to maintain normal glucose homeostasis. The most common form of the disease is type 2 diabetes (T2D), a progressive metabolic disorder characterized by elevated glucose levels that develops in response to either multi-organ insulin resistance or insufficient insulin secretion from pancreatic β-cells. Although the etiology of T2D is complex, many factors are known to contribute to defects of glucose homeostasis, including obesity, unhealthy lifestyle choices, genetic susceptibility, and environmental exposures. In addition to these factors, noncoding RNAs (ncRNAs) have been recently implicated in the pathogenesis of T2D, playing roles in several of the pathophysiological mechanisms underlying the disease, particularly in insulin-sensitive tissues such as pancreatic β-cells, liver, muscle, and adipose tissue. A growing number of publications demonstrate that polymorphisms in ncRNAs or their target genes may represent a new class of genetic variation contributing to the development of T2D. This review summarizes both the current state of knowledge of ncRNAs, specifically microRNAs (miRNAs), involved in the regulation of β-cell function, insulin sensitivity, and insulin action in peripheral organs. The role of genetic variation in miRNAs or miRNA binding sites in the pathogenesis of T2D is also discussed. While far less is known about the impact of long ncRNAs (lncRNAs) in the development of T2D, emerging evidence suggests that these molecules may be able to contribute to β-cell dysfunction in response to hyperglycemia. This article provides an overview of the studies conducted to date in this field, focusing on lncRNAs that are dysregulated in human pancreatic islets.